MAPPING THE TANGIBLE CULTURAL PROPERTIES OF MARIVELES, BATAAN: BASIS FOR THE DEVELOPMENT OF INFORMATION, EDUCATION AND COMMUNICATION (IEC) MATERIALS - Jhana Mira D. Carillo; Michael Lester D. Calma; Angela Lea P. Causon; Daisy T. Dycoco; Anna Mae Z. Juico; Carmela I. Lava; John Mark H. Olivera (Journal of Governance and Global Studies, 2025)
Cultural mapping has become a part of both the cultural planning and community cultural development. Hence, this study aimed to map the cultural properties of Mariveles, Bataan as a basis for the development of information, education and communication (IEC) materials. This study employed Participatory Cultural Mapping as an approach in gathering and analyzing the data. Following this approach, the researchers worked and collaborated with the owners, caretakers, barangay officials, local tourism officers, and locals who have knowledge about the eleven (11) identified cultural properties. Triangulation method was used to gather and validate information from the participants. The instruments used in this study are the NCCA Cultural Mapping Form, Semi - Structured Interview and Document Analysis. The quantitative definition of cultural inventory was used to interpret the data obtained from the field visits and record study. The findings of this study is divided into two categories such as movable and immovable. First, there are two (2) identified tangible movable cultural properties in Mariveles including Señor Nazareno and St. Nicholas de Tolentino. While nine (9) tangible immovable cultural properties were identified including the Municipal Marker, Mariveles Dam, Copo de Mariveles, Poblacion Lighthouse, Freeport Area of Bataan, Llamas Memorial Institute, Llamas Statue in Antonio G. Llamas Elementary School, Lazareto de Mariveles and US Detachment Stone were documented. In addition, this study resulted in the identification of the significance, problems or constraints, and preservation measures installed to the identified tangible cultural properties. Finally, this study resulted in the development of the Information, Education and Communication (IEC) Materials which can be used in both tourism and education sectors. Based on the results of this study, it is recommended for the Local Government Unit to offer financial help for the refurbishment and maintenance as well as for proper maintenance of the identified cultural properties. For the caretakers of the movable property, the Local Government Unit can assist them on printing materials to disseminate so that other people will be aware about the property. Programs to inform students and citizens of Mariveles about tangible cultural properties must be implemented by the municipal authority. To disseminate the knowledge and to raise awareness about how every cultural property is endangered, old and prone to destruction, the municipality of Mariveles needs to develop more comprehensive, approachable, and creative ways and programs. To create effective and creative IEC materials that can be used by local schools either in elementary or secondary to educate the students about the history and culture of Mariveles.